Relationship between mixing time and concrete strength - M. N., Ikhsan; H. A. A., Sidek; I. M., Pauzi; Z. A., Wahab; A. A., Amry (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.